Peningkatan Mutu dan Sumber Daya Manusia melalui Pembelajaran IPS yang Berkualitas di MTs Nurul Iman - Yenni K Pane (UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to explain the relevance between quality improvement and human resources through quality Social Science learning at MTs Nurul Iman, Deli Serdang Regency, North Sumatra Province. Improving the quality of students can be through quality Social Science learning and this can be realized if the human resources in schools are also of high quality. This research uses descriptive qualitative research. Data were collected through literature study, observation, document analysis and interviews. Data analysis uses an interactive model from Miles and Huberman. The results show that there is a relevance between improving quality and human resources through quality Social Science learning. If quality Social Science learning can be created, then it will also affect the quality of human beings and the quality of education. This study recommends that schools focus more on improving human resources, including principals, teachers, and administrative staff, and then creating quality learning.